2023
DOI: 10.1140/epjs/s11734-023-00933-2
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic scattering of hydrogen atoms off pristine and hydrogen-covered W(100) surfaces

Abstract: Recent experiments have shown that translational energy loss is mainly mediated by electron-hole pair excitations for hydrogen atoms impinging on clean metallic surfaces. Inspired by these studies, quasi-classical trajectory simulations are here performed to investigate the energy transfer after scattering of hydrogen atoms off clean and hydrogen-covered tungsten (100) surfaces. The present theoretical approach examines the coverage effect of the preadsorbed hydrogen atoms, as was done recently for the (110) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…For this crystallographic plane, most of the reflecting atoms bounce off the second layer tungsten atoms at zero coverage. 27 This contribution decreases with an increasing coverage. At specular angles, only 8.8% of the scattered atoms make their first rebound on top on a tungsten surface atom for θ = 0 ML, while 90.2% do so at θ = 2 ML coverage.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…For this crystallographic plane, most of the reflecting atoms bounce off the second layer tungsten atoms at zero coverage. 27 This contribution decreases with an increasing coverage. At specular angles, only 8.8% of the scattered atoms make their first rebound on top on a tungsten surface atom for θ = 0 ML, while 90.2% do so at θ = 2 ML coverage.…”
Section: Resultsmentioning
confidence: 95%
“…These studies have also confirmed the validity of MDEF in rationalizing H scattering from metals. ,, Such a theoretical framework has thus been used recently to investigate H atom scattering off H-covered tungsten surfaces, focusing both on energy transfers ,, upon scattering and Eley–Rideal and Hot-Atom recombination dynamics, the H-Tungsten system being currently of prime interest for its implication in nuclear fusion technologies. , Previous works have shown that H-coverage increases the energy transfers and Hsticking probability at the surface. As highlighted in the following, this is the consequence of the very effective extra dissipation channel via binary collision between the impinging atoms and the adsorbates. , However, a completely different scenario is predicted when considering scattering at specular angle , for which reflection probability increases and energy loss decreases. Scattering at such an angle is of special importance as experiments usually allow to measure only in the scattering plane and, if collisions are carried out at a few eV, specular scattering typically leads to a maximum of signal …”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations